Immediate Effects of Release Ball Massage and Self-stretching Exercise on Hamstring’s Temperature, Range of Motion and Strength in 20’s Women - Jeong, Younghun; Park, Jihwan; Yu, Jin; Lee, Sunyeong; Ha, Jihee; Choo, Yeonki; Oh, Taeyoung (Journal of International Academy of Physical Therapy Research, 2019)
Background: There have been many studies on self-myofascial release (SMR) stretching, but there are few comparative studies on the effects of massages using a release ball, which is a type of the SMR method. Objective: To investigate the immediate effects of release ball massage and self- stretching on proprioceptive sensory, hamstring’s temperature, range of motion (ROM) muscle strength,. Design: Crossover study. Methods: Thirty women in 20’s at S University in Busan voluntarily participated in the study. Participants were random to release ball group (n=15) or selfstretching group (n=15). Both groups performed 3 sets of exercises, stretching for 30 seconds and resting for 15 seconds in each position. The proprioceptive sensory, temperature of the hamstring muscle, ROM, and strength were measured before exercise, 5 minutes after exercise, and 30 minutes after exercise. Results: Release ball group showed significant differences in muscle length and temperature over time (p<.05). The comparison between two group over time showed significant differences in muscle length, temperature, and muscle strength (p<.05). Conclusions: These results demonstrate that release ball massage and selfstretching are beneficial for improving hamstring's temperature, ROM and muscle strength. KCI Citation Count: 0